Pengaruh Program Keluarga Harapan (PKH) Terhadap Penanggulangan Kemikinanan di Kota Metro (Studi Kasus Kecamatan Metro Barat) - Hasanah, Uswatun; Suhada, Bambang (Universitas Muhammadiyah Metro, 2022)
This study aims to determine the factors that influence the Family Hope Program (PKH) on Poverty Reduction in Metro City, Metro Barat District. This type of research is quantitative research, data collection is obtained from the results of questionnaires from 84 community respondents who received the Family Hope Program (PKH) assistance taken using a simple sampling technique formula, research data analysis was carried out using quantitative data analysis by testing instrument requirements, analysis requirements and hypothesis. The results of the study show that the Family Hope Program (PKH) variable has a positive and significant effect on poverty alleviation in the people of West Metro District